Renewable Energy in Developing Countries Local Development and Techno-Economic Aspects (Green Energy and Technology,, 2018)
This book discusses aspects of policy and techno-economic analysis of renewable energy in developing countries. Renewable energy technologies have been one of the most important strategies in addressing sustainable energy development and climate change. The roles of renewable energy in developing countries are vital, which include the accessibility of modern energy services in rural areas, climate change mitigation, energy security, green job creation and eventually improvement of quality of life. Part I of this book focuses on policy and strategy, while Part II focuses on technology development and feasibility. Chapters are contributed by leading experts from the ASEAN Center of Energy, government agencies, industries, and universities from five developing countries, including Malaysia, Indonesia, Vietnam, Brunei Darussalam and Bangladesh.